2017
DOI: 10.1111/ter.12259
|View full text |Cite
|
Sign up to set email alerts
|

When the earth blisters: Exploring recurrent liquefaction features in the coastal system of Christchurch, New Zealand

Abstract: The 14 February, or Valentine's Day, 2016 earthquake located offshore of Christchurch produced a new generation of liquefaction in the coastal environment of Christchurch, an environment of recurrent liquefaction during the 2010-2011 Canterbury Earthquake Sequence. The Valentine's Day earthquake occurred while trenches were open at a site in the coastal environment for studying the 2010-2011 liquefaction features. Observations in the 2016 trenches provided insights into the formation of a suite of surface and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In contrast, the coastal dune soils are characterized by well to moderately sorted fine and medium sandy sediment (Giona Bucci et al ., ) and by an intergrain–microaggregate or close packing microstructure, locally single grain (no fine material bounding the grains) or bridged (presence of fine material bridging the grains; Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the coastal dune soils are characterized by well to moderately sorted fine and medium sandy sediment (Giona Bucci et al ., ) and by an intergrain–microaggregate or close packing microstructure, locally single grain (no fine material bounding the grains) or bridged (presence of fine material bridging the grains; Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies following 14 February 2016 (after the QEII trenching campaign) showed that the ‘L2 unit’ observed at QEII park is a type of liquefaction feature, namely sand sills that split A‐horizons in the coastal dune setting (Giona Bucci et al ., ). While the A‐horizon splitting in QEII had a small dyke associated with it, other similar features may not have them (as a liquefiable source layer can be immediately below the A‐horizon).…”
Section: Discussionmentioning
confidence: 97%
“…The reader is referred to the overviews of field interpretation by Obermeier et al (2001, 2005), and to the studies of Sims (1973), Obermeier and Dickenson (2000), Cox et al (2007), Tuttle et al (2002, 2005, 2019b), Tuttle and Atkinson (2010), Giona Bucci et al (2018a, 2018b), and Villamor et al (2016) for specific case studies. In addition, Sims and Garvin (1995), Quigley et al (2013), Bastin et al (2016), Giona Bucci et al (2017), Tuttle et al (2017), and Maurer et al (2019) discuss field interpretation specific to spatiotemporally clustered earthquakes. Once identified, paleoliquefaction features may be dated via radiocarbon, optically stimulated luminescence, archeological context, stratigraphic context, or soil development indicators, such as weathering and biologic activity, among others.…”
Section: Introductionmentioning
confidence: 99%